WAY OF WISDOM: A WAY OF SPIRITUALITY - Waldenfels, H. (Journal of Dharma, 1988)
Today the question of wisdom is raised in the East and the West anew. It covers, on the one hand, the question of the relationship between philosophy and religion, and philosophy and theology. It includes, on the other hand, the question of the foundation of our existence and the world. Wisdom, however, cannot be treated without treating love, enlightenment, not without compassion.